Collagen vascular diseases associated with interstitial lung diseases : analysis of alveolar epithelial cellular stress mechanisms - Kramer, Barbara; Justus Liebig University Giessen (My University, 2017)
Interstitial lung diseases (ILD) or diffuse parenchymal lung diseases (DPLD) are a heterogenous group of chronic disorders that affect the distal lung. They are largely unresponsive to any currently available therapy and lead to architectural distortion of the lung parenchyma and rapid respiratory failure. The pathogenesis of the disease is not completely understood. In some ILDs like the idiopathic pulmonary fibrosis (IPF) the initial alveolar epithelial cell injury followed by ER-stress and apoptosis of alveolar epithelial cells type II (AECII) seems to be the triggering factor. Collagen vascular diseases (CVD) are a group of immunologically mediated inflammatory disorders affecting predominantly the connective tissue and the vessels, however, quite frequently, also the lung. Especially in Polymyositis (PM), Dermatomyositis (DM) and Systemic Sclerosis (SSc), ILD determines morbidity and mortality of the disease. Autoantibody expression seems to be highly predictive for pulmonary involvement. An autoantibody frequently found in PM/DM is anti histidyl-tRNA-Synthethase (anti-HisRS), most specific autoantibodies in SSc are anti-Topoisomerase1 (anti-Topo1), anti-Topoisomerase2alpha (anti-Topo2alpha) and anti-Topoisomerase2beta (anti-Topo2beta). In the present project it was hypothesized that autoantibodies cause development of ILD in CVD via alveolar epithelial cell injury leading to an ER-stress and apoptotic response in AECIIs. We supposed that the binding of pathogenetic antibody directed against HisRS and topoisomerases results in a loss of function of the respective proteins, which again causes aleveolar epithelial cell injury. In order to evaluate such proposed mechanism, HisRS, Topo1, Topo2alpha and Topo2beta were silenced via siRNA transfection in vitro in A549 cells. Furthermore, inhibition of topoisomerases was performed in vitro by treating A549 cells with topotecan and etoposide. ER-stress and apoptosis were analyzed employing Western Blot, semiquantitative RT-PCR and quantitative RT-PCR.In vitro knockdown experiments (siRNA mediated) for HisRS, Topo1, Topo2alpha and Topo2beta did not result in ER-stress or increased apoptosis markers. On the other hand it was shown that ER-stress and apoptosis occur in A549 cells after inhibition of topoisomerases with topotecan or etoposide. Performing immunohistochemistry of lung sections of a patient with SSc associated ILD revealed ER-stress and apoptosis in AECIIs. These results suggest that autoantibodies found in CVD may contribute to the development of ILD by causing ER-stress and apoptosis in AECIIs.

Die interstitiellen Lungenerkrankungen (englisch: ILD- interstitial lung disease) sind eine heterogene Gruppe von chronischen Lungenerkrankungen, die das periphere Lungenparenchym betreffen. Im Falle einiger ILDs wie der idiopathischen pulmonalen Fibrose (IPF) sind diese überwiegend therapierefraktär, führen zu Zerstörung der Architektur des Lungenparenchyms und rasch zu respiratorischem Versagen. Obwohl die Pathogenese der Erkrankung größtenteils ungeklärt ist, lassen neue Studien gerade bei der so ungünstigen IPF eine initiale Schädigung von Alveolarepithelzellen (AEC) vermuten, woraufhin es zu ER-Stress und Apoptose von Alveolarepithelzellen Typ II (AECII) kommt. Bei Kollagenosen, einer Gruppe von Autoimmunerkrankungen, die sich bei systemischem Befall vorwiegend an Bindegewebe und Blutgefäßen abspielen, stellt die Entwicklung einer ILD eine nicht seltene Komplikation dar. Vor allem bei den Kollagenosen Polymyositis (PM), Dermatomyositis (DM) und systemischer Sklerose (SSc) bestimmt wesentlich das Vorhandensein einer ILD die Morbidität und Mortalität der Erkrankung. Die pulmonale Beteiligung ist mit dem Auftreten spezifischer Autoantikörper (AAk) assoziiert. Bei PM/DM handelt es sich um AAk gegen Histidyl-tRNA-Synthethase (HisRS), spezifische AAk bei SSc sind gegen die Topoisomerase1, 2alpha und 2beta (Topo1/2alpha/2beta) gerichtet.Für das hier vorliegende Projekt wurde die Hypothese aufgestellt, dass die AAk zur Pathogenese der ILDs in Kollagenosen beitragen, indem sie das alveoläre Epithel schädigen im Sinne eines ER-Stress und so zur Apoptose der AECIIs führen. Wir postulierten, dass die Bindung der spezifischen Autoantikörper an HisRS und die Topoisomerasen zu einem Funktionsverlust der jeweiligen Proteine führt und so ein Schaden im Bereich des alveolären Epithels verursacht wird. Daher wurden die Zielgene der genannten AAk in vitro in A549 Zellen mit entsprechenden siRNA gehemmt. Außerdem wurde ein Funktionsverlust der Topoisomerasen durch Behandlung von A549 Zellen mit Topotecan und Etoposide erzielt. Mittels Western Blot, semiquantitativer und quantitativer PCR wurden anschließend ER-Stress- und Apoptose-Marker analysiert. Die in vitro Hemmung der AAk durch eine siRNA Transfektion ergab keinen deutlichen Effekt bezüglich ER-Stress und Apoptose. Allerdings konnte gezeigt werden, dass nach der Inhibition von Topoisomerasen durch Topotecan und Etoposide eine deutliche ER-stress- und Apoptose-Antwort in A549 Zellen stattfindet. Im Rahmen der immunhistochemischen Untersuchung von Lungenschnitten eines Patienten mit SSc assoziierter ILD hinsichtlich zellulärer Stressmuster konnten ER-Stress und Apoptose in den AECIIs dargestellt werden. Die vorliegenden Ergebnisse legen die Vermutung nahe, dass die in Assoziation mit genannten Kollagenosen auftretenden AAk die Entwicklung von ILDs vermitteln können, indem sie ER-Stress und Apoptose in AECIIs auslösen.
Keywords: ddc:610